Soil quality assessment and management plans for IITA research farms, Nigeria: IITA Ibadan campus, Ikenne and Kano (Minjibir) stations - Huising, J.E.; Mesele, S.A. (International Institute of Tropical Agriculture, 2021)
This document contains a summary of the observations and results of the IITA research farms soil assessment. This report also includes the proposed soil management plans for each of the research farms. The field observation data, soil and water laboratory results are presented in the Appendix.